Comparative growth performance of mixed-sex and monosex Nile tilapia at various stocking densities during cage culture - Chakraborty, Suman Bhusan; Banerjee, Samir (Recent Research in Science and Technology, 2013)
Information related to impact of stocking density on growth performance of androgen-treated monosex Nile tilapia, Oreochromis niloticus during cage culture in West Bengal, India is limited. The aim of this study was to compare the growth potential of mixed-sex control and hormone-treated monosex tilapia at various stocking densities and to determine an ideal stocking density for cage culture of monosex fish. Mixed-sex control and 17α-methyltestosterone treated monosex tilapia were stocked separately in standing surface cages at different stocking densities (1, 5, 10, 15, 25, 50, 75 and 100 fish/m3). At the end of 5-month culture period, the highest growth was observed in the 50 fish/m3 groups for both the control and hormone treated categories. More over, the monosex androgen treated tilapia in each density class showed significantly higher (P-value < 0.05) weight, length and depth compared to mixed-sex fish in the corresponding density class. The survival rate of the fish did not alter significantly with hormone treatment but stocking density had significant effect (P-value < 0.05) on it. Thus, cage culture of hormone treated monosex tilapia at a density of 50 fish/m3 may be considered ideal for augmented production of the fish under Indian context.